Assessment of biohydrogen injection system through Arduino setting in photosynthetic and dark fermentation by local microalgae culture - Kamrul Fakir, Kamarudin; Nur Farah, Mohd Shukuri; Nazlina Haiza, Mohd Yasin; Suresh, Thanakodi; Azizi, Miskon; Mohd Sobri, Takriff (Penerbit Universiti Kebangsaan Malaysia, 2021)
Biohydrogen (a hydrogen gas produced by biological methods) is one of the most sustainable sources of energy for electricity generation. Hydrogen gas combustion produces only water without the release of greenhouse gases emission. Microalgae are the microorganisms that can produce biohydrogen through photosynthesis and dark fermentation. In this study, the local microalgae isolate, Chlamydomonas sp.UKM6 has been used to generate biohydrogen using both fermentation methods under anaerobic conditions. Photosynthesis fermentation was carried out using the live culture of UKM6 under continuous illumination while dark fermentation was carried out using the biomass of UKM6 with the palm oil mill effluent (POME) sludge as an inoculum. The resulting hydrogen gas is automatically injected into the fuel cell system using the newly developed Arduino Uno. Using data presented from the Arduino settings program, the biomass of UKM6 in dark fermentation produces the highest hydrogen gas and voltage at 30.89 ppm and 0.92 mV, respectively. Based on the results, it can be concluded that microalgae have the potential to generate energy through the production of biohydrogen which can be further analyzed using fuel cell technology. This system can be further improved in the future to measure energy generated directly and effectively.